Measuring situational triggers of television channel switching - Phau, Ian; Dix, Steve (Emerald Group Publishing Limited, 2010)
Purpose: The purpose of this paper is to describe the development of a scale (SITUZAP) to measure the situational factors that trigger channel switching, specifically within the television environment. Design/methodology/approach: The domain construct is defined and 14 potential scale items were drawn from the literature and qualitative research. The scale was purified during the pilot phase and three scale items removed. The scale was re‐tested during the main study via an independent sample, confirming the two‐dimensional nature of the scale. Findings: Reliability analysis indicates that the scale is internally consistent with co‐efficient alpha high across both pilot and main studies. Moreover, confirmatory factor analysis supports the two‐factor measurement model – “advertising triggers” and “RCD empowerment”. The test‐retest result (r=0.662) further provides evidence of stability within the scale. The scale has also been verified for content, criterion, discriminant, and nomological validity. All other indicators are within the acceptable range of statistics. Originality/value: This is the first scale that measures the effect of situational factors on channel switching.